Gap Produktivitas Menurut Gender Pada Petani Padi di Indonesia - Kadir, Kadir; Prasetyo, Octavia Rizky (Seminar Nasional Official Statistics, 2023)
Our study aims to confirm the gender yield gap in the context of paddy cultivation in Indonesia by estimating the gap between female and male farmers and decomposing it to identify the explained contributing factors. Using the results of the SUTAS, we found that female farmers’ yield is lower by about 2.3 percent on average than their male counterparts. Decomposition results of Blinder-Oaxaca and Counterfactual Distribution pointed out that most of the gap can be explained by the difference in characteristics between the two groups, particularly in educational attainment and mechanization adoption, in which female farmers lag behind. We found that the gap tends to be wider at the bottom of yield distribution. Our findings suggest, improving female farmers' education and their technology adoption are key to covering the gap. However, a substantial proportion of the unexplained gap could be an indication that there is negative discrimination against female farmers.